The IPO of Uber - a classroom case. (19th October 2020) - Cordina, Renzo; Feng, Jingjian; Hannah, Gwen; Power, David M.
This case looks at the initial public offering (IPO) of 180 m shares in Uber Technologies Inc. on May 9th 2019. It considers why the company was seeking to list its shares on the New York Stock Exchange (NYSE) at this time and the possible issue price for these shares using valuation multiples from a competitor (Lyft Inc.) that was already listed. The difficulties associated with valuing Uber's IPO are examined by considering the legal, regulatory, staffing and other problems which affected the company at this time. This case considers whether Uber had the characteristics of an unsuccessful IPO. The main purpose of this case is to highlight how the first-day returns for the IPO performed poorly relative to findings from the literature about past IPOs. Finally, the case considers possible explanations for the poor first-day returns.